Feondlice wiccan, wisum dryum, and yfelre leodrunan - Lexical Variation and Syntagmatic Relations of the Old English Lexical Field of WITCH - Räsänen, Ida (My University, 2019)
In this thesis I study the Old English words that mean ‘witch’, the distribution of the words in Old English texts and what kind of other words are connected to them, in order to determine how the different words are used and how witches were talked about and perceived in Anglo-Saxon England. The aim is to discover if some of the words are preferred over others and in what kind of contexts and cotexts the words appear. The 28 words meaning ‘witch’ form a lexical field as presented by the lexical field theory, first developed by Jost Trier in the 1930s. The lexical field is examined through the means of lexical variation analysis, with a focus on contextual features such as genre, author, date, and dialect of the texts in which the words under study appear. The lexical variation analysis is followed by an analysis of the syntagmatic relations the words have with adjectives, noun, and verbs they are accompanied with. Out of the 28 words, dry, drymann and wicca stand out as the most common, and the most common genre of the texts is religious prose. The syntagm analysis reveals that most of the words connected to the ‘witch’ words are either neutral or negative, with the concept of ‘deceit’ appearing in all perspectives of the analysis, indicating that witches were seen and portrayed as deceitful.
Keywords: lexical field, lexical variation, Old English, syntagm, witch